Audit performance alignment analysis of the supreme audit institution of Indonesia (BPK) with the new public management (NPM) concept - Welliya Elfajri; Harif Amali Rivai; Fajri Adrianto (Enrichment : Journal of Management, 2023)
This research is aimed at assessing how the Supreme Audit Institution of Indonesia (BPK) places emphasis on the direction of the audit to be carried out. This study uses a descriptive qualitative method by conducting a performance comparison analysis on audit performance conducted by the BPK in 2020-2021. The research data is secondary data in the form of BPK Audit Results Summary (IHPS) data. The results of this study indicate that there is no visible consistency in increasing performance audits from 2020-2021, decreasing in 2020, then increasing in 2021. However, the increase in performance audits that occurred in 2021 shows that when conditions are getting better, BPK is increasingly focused on developing performance audits, which can be interpreted as making more efforts to align the direction of audit performance with the New Public Management (NPM) concept.